4x+3 chia hết cho 2x-1
=> 4x-2+5 chia hết cho 2x-1
=> 2(2x-1)+5 chia hết cho 2x-1
mà 2(2x-1) chia hết cho 2x-1
=> 5 chia hết cho 2x-1
=>2x − 1 ∈ Ư 5 = 1;5
=> 2x ∈ 2;6
=> x ∈ 1;3
:D
mk cho bài kham khảo nha :
4x+3 chia hết cho 2x-1
=> 4x-2+5 chia hết cho 2x-1
=> 2(2x-1)+5 chia hết cho 2x-1
mà 2(2x-1) chia hết cho 2x-1
=> 5 chia hết cho 2x-1
=>\(2x-1\inƯ\left(5\right)=\left(1;5\right)\)
=> \(2x\in\left(2;6\right)\)
=> \(x\in\left(1;3\right)\)
:D
4x + 3 \(⋮\) 2x - 1 <=> 2(2x - 1) + 5 \(⋮\) 2x - 1
=> 5 \(⋮\) 2x - 1 (vì 2(2x - 1) \(⋮\) 2x - 1)
=> 2x - 1 \(\in\) Ư(5) = {1; 5}
2x - 1 = 1 => 2x = 2 => x = 1
2x - 1 = 5 => 2x = 6 => x = 3
Vậy x \(\in\) {1; 3}
4x + 3 chia hết cho 2x - 1
=> ( 4x - 2 ) + 5 chia hết cho 2x - 1
=> 2 ( 2x - 2 ) + 5 chia hết cho 2x - 1
mà 2 ( 2x - 2 ) chia hết cho 2x - 1
=> 5 chia hết cho 2x - 1
=> 2x - 1 thuộc Ư(5) = { -5 ; -1 ; 1 ; 5 }
Ta có :
2x - 1 | -5 | -1 | 1 | 5 |
2x | -4 | 0 | 2 | 6 |
x | -2 | 0 | 1 | 3 |
:D